Perencanaan Strategis Sistem Informasi Dan Teknologi Informasi Koni Buleleng - Manohara, Gede Raditya; Pradnyana, I Made Ardwi; Dantes, Gede Rasben (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Komite Olahraga Nasional Indonesia (KONI) Buleleng is a branch of the Central KONI which functions as managing, fostering, and developing sports in Buleleng Regency. To create modern operations, KONI Buleleng hopes to implement appropriate information systems and information technology (IS/IT). The purpose of this research is to realize the appropriate implementation of SI/TI KONI Buleleng for the future through the practice of strategic planning. Strategic planning of IS/IT KONI Buleleng is implemented through Ward and Peppard method approach which consists of internal business analysis, external business analysis, internal IS/IT analysis, external IS/IT analysis, SI business strategy, IT strategy, IS/IT strategy management, and IS/IT portfolio. Through all these stages, various strategic proposals were obtained such as data integration into the Management Information System and developing chatbots and athlete/coach data visualization dashboards. It is also proposed to procure devices that can help the athlete coaching process such as HR Monitor. KONI Buleleng needs to conduct audits and evaluations of strategic planning and implementation of IS/IT on a regular basis.